2012
DOI: 10.1016/j.clinph.2012.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Brain oscillatory complexity across the life span

Abstract: Objective: Considering the increasing use of complexity estimates in neuropsychiatric populations, a normative study is critical to define the 'normal' behaviour of brain oscillatory complexity across the life span. Method:This study examines changes in resting-state magnetoencephalogram (MEG) complexity -quantified with the Lempel-Ziv complexity (LZC) algorithm -due to age and gender in a large sample of 222 (100 males/122 females) healthy participants with ages ranging from 7 to 84 years.Results: A signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
66
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 66 publications
11
66
0
1
Order By: Relevance
“…Furthermore, the results in Figures 2 and 3 show that the anterior and central regions of the brain generally have higher nPE and nmPE values when compared to other regions of the brain. This was observed for all age groups, and is a result that is in accordance with that obtained by [4]. In the context of the characterisation of healthy ageing, this result suggests that these two brain regions have higher resting state activity than the other three brain regions, and thus have higher entropy than the other brain regions.…”
Section: Evaluation Of Differences Between Npe and Nmpesupporting
confidence: 79%
See 3 more Smart Citations
“…Furthermore, the results in Figures 2 and 3 show that the anterior and central regions of the brain generally have higher nPE and nmPE values when compared to other regions of the brain. This was observed for all age groups, and is a result that is in accordance with that obtained by [4]. In the context of the characterisation of healthy ageing, this result suggests that these two brain regions have higher resting state activity than the other three brain regions, and thus have higher entropy than the other brain regions.…”
Section: Evaluation Of Differences Between Npe and Nmpesupporting
confidence: 79%
“…Various studies analysing healthy males and females [1][2][3][4][61][62][63][64][65] have successfully identified gender as an independent distinguishing characteristic between the gender groups. These studies have shown that significant differences exist between the genders from childhood, to adolescence and adulthood, i.e., throughout life.…”
Section: Gender Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, three illustrative examples show how these tools can be applied to psychology. Keywords Algorithmic complexity · Randomness · Subjective probability · Coding theorem method Randomness and complexity are two concepts which are intimately related and are both central to numerous recent developments in various fields, including finance (Taufemback et al, 2011, Brandouy et al, 2012, linguistics (Gruber, 2010;Naranan, 2011), neuropsychology (Machado et al, 2010;Fernández et al, 2011Fernández et al, , 2012, psychiatry (Yang and Tsai, 2012;Takahashi 2013), genetics (Yagil, 2009;Ryabko et al 2013), sociology (Elzinga, 2010 and the behavioral sciences (Watanabe et al, 2003;Scafetta et al, 2009). In psychology, randomness and complexity have recently attracted interest, following the realization that they could shed light on a diversity of previously undeciphered behaviors and mental processes.…”
mentioning
confidence: 99%